Қaзіргі кезеңдегі Қaзaқстaн Республикaсының сыртқы сaяси істерінің кейбір мәселелері (Халықаралық қатынастар және халықаралық құқық сериясы, 2018)
The article deals with questions of foreign policy activity of Kazakhstanat the present stage. Kazakhstan’s foreign policy are reflected in the «NewKazakhstan’s foreign policy concept of «2014-2020»Approved in 2014,the document was not for the people, for the international communitythan the unprecedented new as president, the competent authorities havealready opened many times in their speeches those tenets and principleson which moves the Republic of Kazakhstan in the international arena. Animportant priority of Kazakhstan’s diplomacy is, and will be the promotionof Kazakhstan’s foreign policy initiatives abroad, and the presentation ofthe global community of Kazakhstan’s economic development model of«Kazakhstan-2050». On the basis of the study documents, authors wereanalyzed and taken further forecast the further direction of foreign policyvector of Kazakhstan.Key words: Republic of Kazakhstan, foreign policy, Kazakhstan’s foreignpolicy concept.